Principles of Islamic Communication in Early Childhood Education - Amin, Afriadi; Kamila, Mahira (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
When people communicate, they seek to achieve shared meaning and share information, ideas, or attitudes with other individuals. If there is no resemblance, there will be a misunderstanding of meaning between the communicator and the communicant; alternatively, the communicant will not catch the message it receives; finally communication will not take place or not communicative. In addition, early childhood, which ranges from one to five years of age, is a very challenging time for children to understand the meaning of language; hence, communication must be considered to ensure that children are not confused. Because the data source for this research is not people but documents, this research uses a qualitative approach. In addition to using documentation techniques, researchers also use comparison methods to find common ground in the process of forming communication principles in early childhood. This research is one example of the type of research conducted in the library (library research). The type of analysis that looks at the substance of the data is called content analysis. The research findings suggest that children enter what is known as a "golden age" at a young age. This is a time when young children are exposed to a variety of stimuli, which this study defines as the "age of wonders." Through clear and consistent communication with children while they are young, we can help them learn to identify and distinguish between right and wrong, making it easier to solve problems, and look out for the best interests of the child. It is hoped that in the future, children will not make wrong decisions about the people they associate with outside the family and will not experiment with activities that can harm themselves or the environment.